Fusional vergence measurements for eso versus exo deviations: is there a difference? - Lança, Carla Costa (2016)
Purpose: The aims of this study were to compare angle of deviation, fusional vergence measurements and fusion reserve ratio between esophoria and exophoria. Methods: A cross-sectional study was performed in children with best-corrected visual acuity of 0.0 LogMAR in either eye, compensated heterophoria within 10 prism dioptres (PD), full ocular rotations, presence of fusional vergence and stereopsis (60 seconds of arc or better). Fusional amplitudes were compared between angle of deviation (2, 4, 6, 8 and 10 PD) in esophoria and exophoria. The fusion reserve ratio was calculated (to assess the effect of the underlying angle of deviation) as fusional convergence divided by prism alternating cover test measurements. Results: Two-hundred and eleven children (7.65±1.16 years) were recruited to this study. Exophoria was most common for near (n=181; 85.8%) and distance (n=20; 9.5%). Esophoria was present in 22 children for near (10.4%) and in 1 child for distance (0.5%). No significant differences were found between fusional amplitudes and angle of deviation for near (p>0.05). Children with exophoria of 10PD had a slight, but not, significant (p=0.264) increase in fusional convergence from 2PD (19.95±5.09) to 10PD (26.67±5.77). In esophoric children the variation of fusional convergence was smaller from 2P (25.00±0.00) to 10PD (22.50±3.54) and non significant (p=0.185). The fusion reserve ratio was significantly smaller in children with higher deviations (i.e. 10PD) for both esophoria (p=0.003) and exophoria (p>0.001). The fusion reserve ratio ranged between 12.50 (2PD) and 2.25±0.35 (10PD) for esophoria and between 9.98±2.55 (2PD) and 2.67±0.58 (10PD) for exophoria. Conclusions: Angle of deviation is not an efficient measure to predict fusional amplitudes. The fusion reserve ratio appears to be a better measurement to assess the effect of the underlying angle of deviation on fusional convergence. More studies are necessary to understand better the relationship between fusion amplitudes and angle of deviation.